When TikTok Becomes the Therapist: Interpersonal Meaning in Relatable Content that Influences Viewers’ Emotions - Rahayu, Jihan Paramitha; Jaelani, Alan; Shabir, M (UICELE, 2026)
Studies on TikTok have mainly discussed emotional expression, audience engagement, and digital discourse separately, while limited research integrates Systemic Functional Linguistics’ interpersonal meaning to examine how relatable TikTok content influences viewers emotionally. This study aims to analyze how interpersonal meaning is constructed in relatable TikTok videos and how linguistic choices affect viewers’ emotions. This study employed a descriptive qualitative method using the Systemic Functional Linguistics framework, focusing on interpersonal metafunctions, namely mood, modality, and appraisal. The data consisted of ten relatable TikTok videos discussing themes such as relationships, overthinking, insecurity, healing, and self-worth. Data were collected through transcription of verbal and visual texts and analyzed using interpersonal meaning and Appraisal frameworks. The findings reveal that declarative mood is the most dominant linguistic feature, functioning to express personal experiences and emotional confessions that create emotional closeness with viewers. Modality, especially probability modality such as maybe and sometimes, is used to soften statements and increase empathy. In addition, appraisal resources, particularly affect and judgement, contribute to emotional validation, reassurance, and viewers’ sense of relatability. These findings indicate that relatable TikTok content functions as a form of emotional support or “digital therapist” by constructing empathy and emotional resonance through language. This study suggests that viewers should develop critical awareness toward emotionally persuasive digital content, while future researchers are encouraged to explore multimodal aspects such as visuals, music, and gestures in constructing interpersonal meaning on social media platforms.